RHEED Transmission mode and pole figures : thin film and nanostructure texture analysis - Wang, Gwo-Ching (Springer New York, 2014)
This unique book covers the fundamental principle of electron diffraction, basic instrumentation of RHEED, definitions of textures in thin films and nanostructures, mechanisms and control of texture formation, and examples of RHEED transmission mode measurements of texture and texture evolution of thin films and nanostructures. Also presented is a new application of RHEED in the transmission mode called RHEED pole figure technique that can be used to monitor the texture evolution in thin film growth and nanostructures and is not limited to single crystal epitaxial film growth. Details of the construction of RHEED pole figures and the interpretation of observed pole figures are presented.  Materials covered include metals, semiconductors, and thin insulators. This book also: Presents a new application of RHEED in the transmission mode Introduces a variety of textures from metals, semiconductors, compound semiconductors, and their characteristics in RHEED pole figures Provides examples of RHEED measurements of texture and texture evolution, construction of RHEED pole figures, and interpretation of observed pole figures RHEED Transmission Mode and Pole Figures: Thin Film and Nanostructure Texture Analysis is ideal for researchers in materials science and engineering and nanotechnology.